A new species Eriope orlandoi (Lamiaceae) from the Chapada Diamantina of Bahia, Brazil - Harley, Raymond Mervyn (Phytotaxa, 2023)
Ongoing fieldwork has revealed that further new species of Eriope remain to be published. After a brief introduction, a new species from the Chapada Diamantina is described and illustrated.